KONDISI KRITIS LADA PUTIH BANGKA BELITUNG DAN ALTERNATIF PEMULIHANNYA - Usman Daras; D. Pranowo (Badan Penelitian dan Pengembangan Pertanian, 2009)
Critical condition of muntok white pepper of Bangka Belitung and its alternative recoveryBangka Belitung (Babel) Province is one of the pepper producing areas in Indonesia, particularly for white pepper. Recently, its role however tends to lower indicated by the decreases in cultivation areas and production of white pepper. A number of factors causing the decrease of production and plated area of pepper in Babel are fluctuation of pepper price, infestation of plant diseases, uncontrolled exploitation of tin mining, and expansion of other estate crops. If the factors are not able be controlled carefully, it may result in muntok white pepper, the trademark of Babel, be eliminated over the time or neglected. Hence, a number of alternative solutions such as zoning of main crops growing, diversification of crop production, and strengthening of capital and institutional supports may be established to minimize the decreases of black pepper areas in Babel.